Acute Kidney Injury Risk and Contrast Volume in Intact Versus Ruptured Endovascular Aneurysm Repair in the Vascular Quality Initiative. (August 2022) - LaFontaine, Samantha; Goriacko, Pavel; Carnevale, Matthew; Shukla, Harshal; Phair, John; Indes, Jeffrey; Lipsitz, Evan; Koleilat, Issam
Objective: Renal impairment after repair of ruptured abdominal aortic aneurysm has been associated with post-operative mortality. Acute kidney injury (AKI) risk specifically related to contrast administration in endovascular aneurysm repair (EVAR) for intact vs ruptured aneurysms has not been previously described. It was our objective to evaluate the risk of AKI and the association with contrast administration in EVAR for ruptured (rEVAR) and intact (iEVAR) aneurysm repair in the Vascular Quality Initiative (VQI). Methods: Adult patients less than 90 years old undergoing EVAR in the VQI without prior abdominal aortic surgery or who were not actively on dialysis preoperatively were included. Patients immediately converted to an open repair were excluded. Patients were grouped by repair urgency, and patient and operative characteristics and outcomes compared. Univariable and multivariable analyses were performed to identify factors associated with the primary outcome of AKI. Survival was evaluated by Kaplan-Meier analysis. Results: Of 38, 775 EVAR patients identified, 86.5% underwent elective surgery for an intact aneurysm, 8.4% had urgent surgery for a symptomatic, intact aneurysm, and 5.1% had emergent repair for a ruptured aneurysm. Significant risk factors for AKI included contrast volume, a preoperative eGFR <30 mL/min, procedure urgency, COPD, congestive heart failure (CHF), and total procedure time. The factor most associated with AKI was aneurysm rupture prior to repair (OR 8.6, CI 7.2-10.3, P <.01). The association of contrast volume with the outcome was the least strong with a 4% increase in risk per 25 mL of contrast (OR 1.04, 95% CI 1.01-1.07). With the development of AKI, postoperative survival was reduced regardless of indication. Conclusions: Of all factors assessed, aneurysm rupture was the most and contrast volume the least associated with AKI after EVAR. Further studies should evaluate methods of preventing post-EVAR AKI.